Pola Pemberian MP-ASI dan Status Gizi Bayi Usia 7–24 Bulan - Nurun Ayati Khasanah; Fitria Edni Wari; Ernawati (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2026)
The introduction of complementary feeding (MP-ASI) before the recommended age may increase the risk of health complications in infants, including gastrointestinal infections such as gastroenteritis, which can potentially be fatal. This study aimed to examine the association between complementary feeding practices and the nutritional status of children aged 7–24 months in Mojodadi Village, Kemlagi District, Mojokerto Regency, in 2024. An analytic observational study with a cross-sectional design was conducted. The sample consisted of 34 infants aged 7–24 months. Data were obtained from secondary sources, specifically the 2024 child nutrition report, which included information on the appropriateness of complementary feeding practices and nutritional status based on the weight-for-age (W/A) indicator. The relationship between variables was analyzed using Fisher’s Exact Test.The results showed that the majority of children received complementary feeding at the appropriate age (after 6 months), totaling 27 respondents (79.4%). Similarly, most children had normal nutritional status, also 27 respondents (79.4%). Fisher’s test yielded a p-value of 0.020, indicating a statistically significant association between complementary feeding practices and the nutritional status of infants aged 7–24 months in the study area.Appropriate implementation of complementary feeding—both in terms of timing and feeding practices—has the potential to improve nutritional adequacy and support children’s physical and cognitive development. Health workers and community health volunteers (posyandu cadres) are encouraged to strengthen parental education through demonstrations of age-appropriate complementary feeding practices and to promote regular growth monitoring for early detection of nutritional problems.